Reduced detection of positive expressions in major depression. (30th June 2016) - Milders, Maarten; Bell, Stephen; Boyd, Emily; Thomson, Lewis; Mutha, Ravindra; Hay, Steven; Gopala, Anitha
Abstract: In patients with depression, negative biases have been reported in various cognitive domains, but few studies have examined whether even detection is affected, i.e. are depressed patients more likely to detect the presence of negative stimuli? This study compared detection of sad and happy faces in patients (n=17) and healthy participants (n=18) using an attentional blink task. Patients with depression detected significantly fewer happy faces than matched healthy participants, but for sad faces the group difference was non-significant. The results suggest that depression may affect the detection of positive stimuli. Highlights: Currently depressed patients completed a rapid serial visual presentation task. Patients with depression were less likely to detect the presence of happy faces than healthy participants. Detection of sad expressions was similar in the patient and healthy comparison groups. The findings suggest that detection of positive stimuli may be impaired in depression.